Differences in demographic, clinical, and symptom characteristics and quality of life outcomes among oncology patients with different types of pain. Issue 4 (April 2016) - Posternak, Victoria; Dunn, Laura B.; Dhruva, Anand; Paul, Steven M.; Luce, Judith; Mastick, Judy; Levine, Jon D.; Aouizerat, Bradley E.; Hammer, Marylin; Wright, Fay; Miaskowski, Christine
Abstract : Abstract: The purposes of this study, in oncology outpatients receiving chemotherapy (n = 926), were to: describe the occurrence of different types of pain (ie, no pain, only noncancer pain [NCP], only cancer pain [CP], or both CP and NCP) and evaluate for differences in demographic, clinical, and symptom characteristics, and quality of life (QOL) among the 4 groups. Patients completed self-report questionnaires on demographic and symptom characteristics and QOL. Patients who had pain were asked to indicate if it was or was not related to their cancer or its treatment. Medical records were reviewed for information on cancer and its treatments. In this study, 72.5% of the patients reported pain. Of the 671 who reported pain, 21.5% reported only NCP, 37.0% only CP, and 41.5% both CP and NCP. Across the 3 pain groups, worst pain scores were in the moderate to severe range. Compared with the no pain group, patients with both CP and NCP were significantly younger, more likely to be female, have a higher level of comorbidity, and a poorer functional status. In addition, these patients reported: higher levels of depression, anxiety, fatigue, and sleep disturbance; lower levels of energy and attentional function; and poorer QOL. Patients with only NCP were significantly older than the other 3 groups. The most common comorbidities in the NCP group were back pain, hypertension, osteoarthritis, and depression. Unrelieved CP and NCP continue to be significant problems. Oncology outpatients need to be assessed for both CP and NCP conditions. Abstract : In this study, 72.5% of the patients reported pain. Of the 671 who reported pain, 21.5% reported only noncancer pain, 37.0% only cancer pain, and 41.5% both cancer and noncancer pain.